The effects of neutron radiation on shape memory properties and oxidation behaviour of a Cu-13Al-4Ni alloy - Tatar, C.; Zengin, R. (Elsevier France-Editions Scientifiques Medicales Elsevier, 2008)
The reverse and forward transformation temperatures and oxidation behavior of neutron irradiated CuAlNi shape memory alloy have been investigated. The alloy was irradiated for 3.6 and 7.2 ks with thermal neutron flux at 8 x 10(12) n cm(-2) s(-1), E > 1 MeV. It was seen from differential scanning calorimetry (DSC) that the forward and reverse transformation temperatures of the martensite double left right arrow austenite were decreased with the applied radiation. Enthalpies of transformation (Delta H heating and Delta H cooling) increase with neutron irradiation. Thermogravimetric measurements were carried out to investigate the kinetics of oxidation. The activation energy of oxidation for alloy was calculated using thermogravimetric data. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: shape memory; thermal conduction; heat capacity; thermal treatment